Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41467-019-13755-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Au nanoparticles on titania through an encapsulation strategy under oxidative atmosphere

Abstract: Supported gold catalysts play a crucial role in the chemical industry; however, their poor on-stream stability because of the sintering of the gold nanoparticles restricts their practical application. The strong metal-support interaction (SMSI), an important concept in heterogeneous catalysis, may be applied to construct the structure of catalysts and, hence, improve their reactivity and stability. Here we report an ultrastable Au nanocatalyst after calcination at 800 °C, in which Au nanoparticles are encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 64 publications
8
118
1
Order By: Relevance
“…Au/TiO 2 has been reported to have a lower resonance intensity than Au particles of a similar size in the absence of strong interaction with surface capping molecules 46 . The metal-support interaction results in a negative charge injection into the metal particles by reducible oxides, and a higher increase in d -electron density at the gold site compared to bare Au nanoparticles 47 . The number of unoccupied Au 5 d 5/2 states near the Fermi level is depleted.…”
Section: Resultsmentioning
confidence: 99%
“…Au/TiO 2 has been reported to have a lower resonance intensity than Au particles of a similar size in the absence of strong interaction with surface capping molecules 46 . The metal-support interaction results in a negative charge injection into the metal particles by reducible oxides, and a higher increase in d -electron density at the gold site compared to bare Au nanoparticles 47 . The number of unoccupied Au 5 d 5/2 states near the Fermi level is depleted.…”
Section: Resultsmentioning
confidence: 99%
“…Tuning the strong metal‐support interactions (SMSIs) between the metal catalyst and oxide support is considered an effective strategy for enhancing catalytic selectivity and stability. [ 2–6 ] There are multiple categories of SMSIs, including metal‐support charge transfer, metal‐support interphase layer formation, and the encapsulation metal‐support interaction, among others. [ 7 ] In particular, the encapsulation interaction shows promise as a potential mechanism for immobilizing oxide‐supported nanoparticle catalysts and controlling their selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…TiOx encapsulation can be identified using scanning tunneling microscopy (STM) and/or low energy electron diffraction (LEED) by the observation of moiré superstructures between the TiOx overlayer and the metal surface, usually on Pd(111) [2,4,13] and Pt(111) surfaces [3,8,9]. In contrast to the relatively easily observed encapsulation on the outer surface of metal particles, only a few studies have conjectured that the metal-oxide support interface was also modified during SMSI [14,15]. It has also been reported that no change in the crystal structure was observed for the Pd-TiO2 interface when encapsulation occurred [16], although this study strictly speaking only confirms that the interface was not changed to the extent that the crystallography or epitaxial orientation was affected.…”
Section: Introductionmentioning
confidence: 99%